Weakened Asian summer monsoon anticyclone related to increased anthropogenic aerosol emissions in recent decades - Kai Qie; Wenshou Tian; Jianchun Bian; Fei Xie; Dan Li (npj Climate and Atmospheric Science)
Abstract The Asian summer monsoon anticyclone (ASMA) traps pollutants from South and East Asia elevated by deep convection, which profoundly influences the atmospheric composition and hence stratospheric chemical processes. Here, we identified a significant weakening of the ASMA in the layer of 70–200 hPa during 1958–2020 and found that the change in anthropogenic aerosol emissions was the dominant external forcing responsible for this weakening trend. Significant increases in anthropogenic aerosol emissions over South and East Asia and decreased aerosol emissions over Central Asia led to a decreased meridional temperature gradient at low-latitudes and an increased meridional temperature gradient at mid-latitudes in the troposphere over the Eurasian continent, resulting in a weakened ASMA. The results based on satellite observations and numerical simulations indicated that the weakened ASMA may affect the spatial distribution of CO and water vapor in the UTLS over Asian summer monsoon region.